Influence of method of VA mycorrhizal inoculum placement on the spread of root infection in field-grown cassava - Sieverding, Ewald (1981)
Three methods of placement of VA mycorrhiza inoculum to cassava were compared in the field in order to determine the effect of inoculation methodology on the spread of the introduced fungus in the soil. The spread of the indigenous fungi and of the introduced fungus, Glomus manihotis, with the roots was monitored at 3 soil depths and 3 distances from the planting stake, during 30 wk. of plant growth, corresponding to a cycle of rainy season-dry season- rainy season. In the dry season highest infection ratings were found in the deeper soil horizons; in the wet seasons they were higher in the surface soil. Placement of the inoculum under the stakes, or planting the stake in the inoculum band, increased root infection and the competitive ability of the introduced fungus in those zones where the inoculum was applied, especially during the 1st 3 mo. of growth. Best lateral spread of the introduced fungus was found with side banded inoculum, especially after the dry season. It is suggested that inoculum should be placed under the stakes at planting and reinoculated in side bands during or after the dry season in order to get best spread of the introduced fungusin the field. (AS)